Valorization of Vegetable Food Waste and By-Products Through Fermentation Processes - Sabater, Carlos; Ruiz, Lorena; Delgado, Susana; Ruas-Madiedo, Patricia; Margolles, Abelardo (Frontiers in Microbiology, 2020)
There is a general interest in finding new ways of revalorizing fruit and vegetable processing by-products. With this aim, applications of industrial fermentation to improve nutritional value, or to produce biologically active compounds, have been developed. In this sense, the fermentation of a wide variety of by-products including rice, barley, soya, citrus and milling by-products has been reported. This minireview gives an overview of recent fermentation-based revalorization strategies developed in the last two years. To aid the designing of new bioprocesses of industrial interest, this minireview also provides a detailed comparison of the fermentation conditions needed to produce specific bioactive compounds through a simple artificial neural network model. Different applications reported have been focused on increasing the nutritional value of vegetable by-products, while several Lactobacillus and Penicillium species have been used to produce high purity lactic acid. Bacteria and fungi like Bacillus subtilis, Rhizopus oligosporus or Fusarium flocciferum may be used to efficiently produce protein extracts with high biological value and a wide variety of functional carbohydrates and glycosidases have been produced employing Aspergillus, Yarrowia and Trichoderma species. Fermentative patterns summarized may guide the production of functional ingredients for novel food formulation and the development of low-cost bioprocesses leading to a transition toward a bioeconomy model.